Microstrip multi-stopband filter based on tree fractal slotted resonator - Manju Bhaskar; Thomaskutty Mathew (Institute of Advanced Engineering and Science, 2019)
This paper presents the design and development of a new microstrip multi-stopband filter based on tree fractal slotted resonator. A single square patch with tree fractal slots of different iterations are employed for realizing dual stopband and tri-stopband filters. The tree fractal slotted resonators are generated from conventional square patch using an iterative tree fractal generator method. First, second and third level iterations of the tree fractal slot resonator are used to design dual and tri-stopband filters respectively. The first level iteration introduced for the tree fractal slot realizes dual bands at 2.64 GHz and 3.61 GHz while the second level iteration provides better stopband rejection and insertion loss at 2.57 GHz and 3.56 GHz. The tri-stopband filter generates three resonance frequencies at 1.53 GHz, 2.53 GHz and 3.54 GHz at third level iteration. By varying the slot length and width of the tree fractal slot, the resonant frequencies can be adjusted and stopbands of the proposed filter can be tuned for the desired unwanted frequency to be rejected. The proposed narrowband filters finds application in removing the interference of GPS and Wi-Max narrowband signals from the allotted bands of other wireless communication systems